The Naturalness of Translation in Translating Short Story Entitled “Drupadi” from Indonesian into English - N L.P.V. Dewi; Asril Mardjohan; Made H Santosa (Universitas Pendidikan Ganesha, 2016)
This study aimed at analyzing the naturalness of translation and finding the percentage of the naturalness of translation in translating short story entitled “Drupadi” from Indonesian into English. The subjects of this study were two native speakers which are come from the native area. Meanwhile, the object of this study was a short story entitled “Drupadi” especially the sentences in both Indonesian and English version. In this study, the researcher used Larson’s theory as the reference of the study in order to analyze the naturalness of translation in short story entitled “Drupadi” from Indonesian into English. The data were obtained by two methods of data collection, namely checklist and interview. The total of the data in this study was 131 sentences and it was analyzed descriptively. The result of this study showed that, 0% of the data is considered to fall into “unnatural” level, 2.29% are considered to fall into “less natural” level, 13.74% of the data belong to the “natural” level, and 83.97% of the data is classified as “highly natural”. Based on the result, it can be concluded that the short story entitled “Drupadi” which has been translated by Tom Hunter from Indonesian into English was in “highly natural” level and it can be used as teaching material for the teacher who teaches language, especially translation.